Highly quantitative serological detection of anti-cytomegalovirus (CMV) antibodies - Alter Harvey J; Drew W Lawrence; Exner Maurice; Ching Kathryn H; Issa Alexandra T; Burbelo Peter D; Iadarola Michael J (Virology Journal, 2009)
Abstract Background Human cytomegalovirus infection is associated with a variety of pathological conditions including retinitis, pneumonia, hepatitis and encephalitis that may be transmitted congenitally, horizontally and parenterally and occurs both as a primary infection and as reactivation in immunocompromised individuals. Currently, there is a need for improved quantitative serological tests to document seropositivity with high sensitivity and specificity. Methods Here we investigated whether luciferase immunoprecipitation systems (LIPS) would provide a more quantitative and sensitive method for detecting anti-CMV antibodies. Four protein fragments of immunodominant regions of CMV antigens pp150 and pp65 were generated as Renilla luciferase (Ruc) fusion proteins and used in LIPS with two cohorts of CMV positive and negative sera samples previously tested by ELISA. Results Analysis of the antibody responses to two of these antigen fragments, pp150-d1 and pp150-d2, revealed geometric mean antibody titers in the first cohort that were 100–1000 fold higher in the CMV positive sera compared to the CMV negative samples (p < 0.0001) and infection status exactly matched the ELISA results for the 46 samples of the first cohort (100% sensitivity and 100% specificity). Two additional antigen fragments, pp65-d1 and pp65-d2 also showed robust antibody titers in some CMV-infected sera and yielded 50% and 96% sensitivity, respectively. Analysis of a second cohort of 70 samples using a mixture of the 4 antigens, which simplifies data collection and analysis, yielded values which correlated well with the sum of the values from the 4 separate tests (rs = 0.93, p < 0.00001). While comparison of the LIPS results from this second cohort with ELISA showed 100% sensitivity, LIPS detected six additional CMV positive samples that were not detected by ELISA. Heat map analysis revealed that several of the LIPS positive/ELISA negative samples had positive LIPS immunoreactivity with 3–4 of the CMV antigens. Conclusion These results suggest that LIPS provides a highly robust and quantitative method for studying anti-CMV antibodies and has the potential to more accurately document CMV infection than standard ELISA.